PERAN MEDIA SOSIAL DALAM MEMBANGUN JARINGAN PROFESIONAL UNTUK WIRAUSAHA GEN Z - Burhanuddin, Muhaimin; Febriati, Farida (PROGRESS, 2026)
Social media has become an essential tool for Gen Z entrepreneurs in building professional networks. With more than 3.6 billion social media users worldwide in 2020, and that number expected to continue to grow, these platforms offer unlimited opportunities to interact, collaborate, and expand business networks. This study uses a literature review method to explore how social media functions as a bridge in building valuable professional connections. Through analysis of various relevant studies, it was found that social media not only facilitates communication, but also helps Gen Z entrepreneurs build reputation and credibility in their industries. By utilizing platforms such as LinkedIn, Instagram, and Twitter, these young entrepreneurs can access information, find mentors, and even discover investors. The results of this study indicate that effective use of social media can be the key to success in running a business, especially in an increasingly competitive digital era.